Management of information in the religious domain through an IVR system - Jamaludin, Zulikha; Kelana, Musafir; Embong, Abdullah; Mahmod, A.Rhaffor (2000)
This paper looks at information management in religious domain using telephone as a communication channel. Telephone was used to access available information from the databases of a religious organization. The interface for the information access was interactive voice response (IVR), which was used for receiving, gathering, distributing, processing information, and managing calls. IVR could function as an excellent agent in managing information for it could trace all information status and the flow of any incoming and outgoing calls. This paper is organized into a few sections, and begins by giving some definitions on a few terminology like information management, IVR and religious domain. It then followed by a short explanation of information management using IVR system in religious domain. The paper argues on the importance of IVR system in religious domain and explains some methodology for building information management using IVR. Finally it shared some insight on the prospect of IVR in religious domain in Malaysia. The focus is given to the religious domain because similar system has been introduced in almost every other field (to name a few, banking, sports, education, and entertainment), except religious field. Religious field is left behind in pursuing information access technology. IVR in religious domain has various benefits to the users as well as to the religious organizations.The demonstration of IVR system for religious domain is being developed using direct connection to the Public Switched Telephone Network (PSTN) and a touch-tone, i.e. the Dual Tone Multi Frequency (DTMF) telephone. The system takes into account seven identified major services out of fourteen (the seven services are yet to be studied in order to determine their practicality and viability in relation to IVR). The services are: (1) information on the imam; (2) registration facility allowing user to register for a certain religious-related course; (3) question and answer of messaging type; (4) short lectures; (5) stories and examples in the history of Islam; (6) recitation of Koranic verses; and, (7) basic information on Islam.For the prospect of implementing IVR in the religious domain, a short random survey by telephone was carried out aiming at gathering users’ perceptions and views. The survey tried to measure the capability of IVR in enhancing: (1) the level of information management in religious domain; (2) the level of religious understanding among the callers, (3) the organization’s image; and, (4) the level of professionalism in managing religious matters. The view and perceptions of 69 subjects were taken into account for the above mentioned purposes. These subjects varied in terms of academic background (undergraduates – associate professors) and ages (22 – 55). The result revealed that the prospect of IVR in the religious domain was very promising.At present, the IVR system in religious domain is being developed in order to study the level of its usage and to find out which services are viable as well as practical. Study of the usability of the system is being planned. However, study on its effectiveness has yet to be carried out for there was no IVR system that had been implemented in any religious organization in Malaysia.